2020
DOI: 10.20344/amp.14118
|View full text |Cite
|
Sign up to set email alerts
|

SARS-COV-2 in Ophthalmology: Current Evidence and Standards for Clinical Practice

Abstract: Introduction: COVID-19 is caused by the coronavirus SARS-CoV-2. Ocular manifestations have been reported including conjunctivitis and retinal changes. Therefore, it is of the utmost importance to clarify eye involvement in COVID-19 in order to help with its diagnosis and to further prevent its transmission. The purpose of this review is to describe the structure and transmission of SARS-CoV-2, reported ocular findings and protection strategies for ophthalmologists.Material and Methods: Literature search on Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In a recent meta-analysis on patients with COVID-19, conjunctivitis was observed in 88.8% of patients with ocular manifestation ( 7 ). The direct exposure of the conjunctiva to extraocular pathogens and the connectivity of the ocular surface mucosa and upper respiratory tract (through the nasolacrimal duct) are considered the main mechanisms for direct infection of conjunctival epithelium and the high prevalence of conjunctivitis ( 12 ). Furthermore, some have suggested that the expression of angiotensin-converting-enzyme-2 (ACE2) in the conjunctival epithelium, aqueous humor, and retina acts as the receptor-binding motif of SARS-CoV and allows the virus for tissue spread ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis on patients with COVID-19, conjunctivitis was observed in 88.8% of patients with ocular manifestation ( 7 ). The direct exposure of the conjunctiva to extraocular pathogens and the connectivity of the ocular surface mucosa and upper respiratory tract (through the nasolacrimal duct) are considered the main mechanisms for direct infection of conjunctival epithelium and the high prevalence of conjunctivitis ( 12 ). Furthermore, some have suggested that the expression of angiotensin-converting-enzyme-2 (ACE2) in the conjunctival epithelium, aqueous humor, and retina acts as the receptor-binding motif of SARS-CoV and allows the virus for tissue spread ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported the detection rate of the virus in 0–11% of ocular swab samples ( 17 ). Nonetheless, the conflicting results considering the presence of virus in the tear does not change the necessity of eye protection for reducing the disease transmission ( 12 , 18 , 19 ). The effective drainage of the ocular surface (as the self-cleaning system) may be responsible for the detachment of the virus from the tear film and pass through the nasolacrimal duct into the nasopharyngeal space.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have recommended the use of Goggles to protect the eyes as a site of COVID-19 transmission. Some studies have mentioned conjunctivitis as an early symptom of COVID-19 (26,27,(124)(125)(126)(127)(128). Refer to Table 8.…”
Section: Ocular Manifestationsmentioning
confidence: 99%
“…The AAO and RCOphth have recommended protection for the mouth and nose (e.g., filtering face piece respirator masks) and eyes (e.g., goggles, face-shields) [67,112]. The use of higher order PPE (i.e., FFP2/3) might be an option, in particular when pre-surgical SARS-CoV-2 screening is not available, however the choice of mask type would generally follow internal institutional protocols [27,90,112,113]. Some of these measures such as goggles, although mandatory, might impede focusing the microscope.…”
Section: Key Points For the Surgerymentioning
confidence: 99%